Drivers of Purchase Intention Among Cosmetic Users: A Study on Influencer Marketing, Brand Image, and Price - Naras, Agrizia Rulanti; Rohman, Fatchur (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this research is to identify the direct and indirect effects of influencer marketing, brand image, and price as the independent variables on purchase intention as the dependent variable. Using non-probability sampling and purposive sampling technique, 140 people of the cosmetics wearer population in Malang City who know about the products of ESQA with the minimum age of 18 years were selected as the respondents of this quantitative explanatory research. The results of the multiple linear regression analysis performed in SPSS 26 indicate that influencer marketing has a positive and significant effect on purchase intention, that brand image has a positive and significant influence on purchase intention, dan that price has a positive and significant impact on purchase intention.